ANALISIS POTENSI SEKTOR BASIS DAN NON BASIS KOTA DUMAI TAHUN 2019 DAN 2021 - Cambera, Aditya Duta; Ali, Asrul; Prasaja, Ahmad Syukron (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2023)
The success of a region in improving its economy can be measured from the growth of the Gross Regional Domestic Product (GRDP) from various existing sectors. This Gross Regional Domestic Product (GRDP) growth occurs if the area has a leading sector or a base sector whose growth rate is relatively fast and has strong competitiveness as well as a non-base sector that has the opportunity to become a base sector if the local government is able to condition the existing opportunities into good results. optimal. This study uses secondary data obtained from the Central Statistics Agency (BPS) of Riau Province in the form of time data before covid-19 and after covid-19 in 2019 and 2021. This research was conducted to identify the basic and non-base sectors in the economic structure of Dumai City in in 2019 and 2021 using the LQ (location quotient) analysis method, the Dynamic Location Quotient (DLQ) method. 12 leading sectors, 3 potential sectors, 1 developing sector and 1 lagging sector, with the base sector having the highest average SLQ index value ≥ 1 and the sector which is a non-base sector with an index value < 1.it can be concluded that the emergence of covid-19 in the city of Dumai did not change the basic sector to non-base based on the SLQ and DLQ analysis using the calculation of the PDRB of the city of Dumai in 2019 and 2020.